Triiodothyronine acts on DAO to regulate pulmonary fibrosis progression by facilitating cell senescence through the p53/p21 signaling pathway - Xiaoshu Guo; Xiaoshu Guo; Kai Xu; Lan Wang; Linke Ding; Wenwen Li; Xinsheng Zhang; Weiming Zhao; Ningdan Wang; Gaiping Wang; Wenyu Zhao; Ivan Rosas; et al. (Frontiers Media S.A., 2024)
BackgroundIdiopathic pulmonary fibrosis (IPF) is the result of multiple cycles of epithelial cell injury and fibroblast activation; currently, there is no clear etiology. Increasing evidence suggests that protein metabolism and amino acids play a crucial role in IPF, but the role of D-amino acids is not yet clear. The aim of this study was to identify novel mediators in order to test the hypothesis that D-amino acid oxidase (DAO) plays a significant role in the pathogenesis of IPF.MethodsWe analyzed DAO gene expression in patients with IPF and mice with bleomycin (BLM)-induced lung fibrosis. We performed in vitro and in vivo assays to determine the effect of DAO on primary type II alveolar epithelial cells from mice and A549 cells.ResultsDAO expression was downregulated in the lungs of IPF patients and BLM-induced fibrotic mice. Treatment with D-serine (D-Ser) or drug inhibition of DAO promoted cell senescence through the p53/p21 pathway. Dao−/− mice showed an intensified fibrotic response, and the anti-fibrotic role of T3 was abolished.ConclusionWe concluded that the DAO-p53/p21 axis might be a key anti-fibrotic pathway regulating the progress of fibrosis and facilitating the therapeutic role of T3.